TI_GERICHTE 15.2013.61 vom 29. Juli 2013 , Legittimazione al ricorso. Beni scoperti successivamente alla chiusura del falimento - TI Tribunale d'appello (2013)
Legittimazione al ricorso. Beni scoperti successivamente alla chiusura del falimento